Monoclonal anti-idiotypic antibodies as functional internal images of enzyme active sites: production of a catalytic antibody with a cholinesterase activity. - Izadyar, L (1993)
Monoclonal antibody 9A8 was selected by immunizing mice with AE-2, a monoclonal antibody directed against the active site of acetylcholinesterase. In accordance with the idiotypic network theory, monoclonal anti-idiotypic antibody 9A8 displayed internal-image properties of the original immunogen, the acetylcholinesterase active site. Hydrolysis of acetylthiocholine and related esters of thiocholine by 9A8 follows saturation kinetics and kinetic parameters were determined. The hydrolytic activity is characterized by a lowered kcat value (81 s-1) and an increased Km value (0.6 mM) when compared with the original enzyme. However, the rate acceleration (kcat/kuncat = 4.15 x 10(8) remains higher than for the esterase activities usually described for catalytic antibodies directed against transition-state analogs. The 9A8 activity exhibits a relaxation of specificity toward both substrates and inhibitors. This specificity does not correspond to a known enzymatic activity. The anti-idiotypic approach should be valuable for producing different structural and functional copies of the same enzyme active site. This should allow further insights into structure-activity relationships. Furthermore, use of chemically modified enzymes as immunogens may result in anti-idiotypic antibodies with catalytic activities not found in the native enzymes.